Vaporization thermodynamics of ionic liquids with tetraalkylphosphonium cations. (January 2019) - Zaitsau, Dzmitry H.; Plechkova, Natalia; Verevkin, Sergey P.
Highlights: Vapor pressures for series of tetraalkylphosphonium based ILs were measured. Vaporization enthalpies at 298 K were derived and tested for consistency. Linear dependence of vaporization enthalpies on alkyl chain length was observed. Procedure for estimation of vaporization enthalpies of P-based ILs was suggested. Quantification of Coulomb and dispersion forces was performed. Abstract: Vapour pressures and vaporization enthalpies of tetraalkylphosphonium ionic liquids with [PF6 ] −, [NTf2 ] −, Cl −, and Br − anions have been measured by using quartz-crystal microbalance and thermogravimetry. Chain-length dependences of the vaporization enthalpies have been established and used for validation of experimental data. Quantification of Coulomb and dispersion forces was performed by comparison with vaporization enthalpies of alkanes and trialkylphosphines.